Pengembangan Kesadaran Teknologi Informasi untuk Mendukung Masa Depan Akademik dan Karier Generasi MAN 4 Bojonegoro - NIDA, NIDA`UL KHASANAH; Dwi Nuraini, Salsabila Putri; Moch. Supriyanto; Mubarrok, Rizqi; Bachtiar A.F., Moch. Azril (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
The interest and understanding of class X-3 students of MAN 4 Bojonegoro towards Informatics Engineering is still low due to lack of knowledge about opportunities and basic concepts of the field. This activity aims to improve understanding and foster students' interest in Informatics Engineering through implementation methods, namely preparation, socialization, evaluation and follow-up. The socialization activity was carried out during informatics subjects. The implementing team consisted of Informatics Engineering students as resource persons and facilitators. The results of the activity showed an increase in pretest and posttest scores as well as student enthusiasm in the discussion, indicating an increase in understanding and interest in the field. As a follow-up, this activity is expected to be the first step for students to explore more deeply the field of information technology